Output-only identification of rigid body motions of floating structures: a case study - Ruzzo, C.; Failla, G.; Collu, Maurizio; Nava, V.; Fiamma, V.; Arena, Felice (Elsevier, 2017)
In order to identify rigid body motions of floating offshore structures, output-only techniques are very useful for developing low-cost intermediate-scale experimental activities directly into the sea, instead of wave tanks. A crucial parameter, however, is the length of the response records used as input for the identification process, since short records may result in significant loss of accuracy, while long ones may be incompatible with the assumption of stationarity of the sea state. This work presents a sensitivity study conducted on a numerical model of a spar structure, identified by means of Enhanced Frequency Domain Decomposition method. An overview on the efficiency of the method is given for various lengths of response record, along with practical indications on the minimum values acceptable.
Keywords: Operational Modal Analysis; Output-only dynamic identification; Enhanced Frequency Domain Decomposition method; Floating spar structures